The Influence of e-WOM on Customer Engagement, Purchase Intention, and Purchase Decision in Online Transportation Services - Muhammad Rahadian Nur Jabbar Rahman; Jono Mintarto Munandar; Istiqlaliyah Muflikhati (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2026)
Background: Online transport services have significant growth potential in Indonesia. Therefore, online transportation companies need to implement appropriate strategies, such as electronic word of mouth (e-WOM), to seize this opportunity. e-WOM is a crucial factor in increasing customer engagement, interest, and the likelihood of using online transportation services. Purpose: This study aims to analyze the influence of e-WOM on customer engagement, purchase intention, and purchase decision to use online transportation services. Method: The data were collected through questionnaires with 230 respondents, using non-probability, purposive sampling. The criteria included people residing in Jabodetabek, aged 18 or older, who used online transportation services and had seen reviews of such services. The study used SEM-PLS to examine the impact of e-WOM on customer engagement, purchase intention, and the decision to use online transportation services. Findings: The study found that e-WOM usefulness and credibility significantly enhanced e-WOM, which, in turn, positively affected customer engagement, purchase intention, and the decision to use online transportation services. Although customer engagement did not significantly influence purchase intention, purchase intention strongly drove purchase decision. Conclusions: The e-WOM adoption variable was proven to be the dominant factor that significantly influenced, both directly and indirectly, customer engagement, purchase intention, and decision in online transportation services. Social media users accepted information from reviews perceived as credible and useful. Research implication: This study highlighted the importance of content-based marketing strategies and credible, helpful forums, with an emphasis on e-WOM. Therefore, companies should build online communities, integrate e-WOM into their digital marketing strategies, and improve the quality of online transportation services.